Navigating Professional and Personal Knowing Through Reflective Storytelling Amidst Covid-19. (December 2022) - Graham, Margaret M.
The paper offers space for dialogue illustrating reflection as lived, exploring both my personal and professional experiences of grief and loss surrounding the death of my Dad from Covid −19. In my role as a nurse educator, I share understandings of reflection in facilitating learning and person centered practices with students. I illustrate my approach with two stories generating a narrative giving testimony to those who have died and highlighting the ensuing grief for those who have cared for older people during the pandemic. The first reflective story has been shared with students and snapshots of student responses during virtual sessions are incorporated. The second story shifts to a more personal focus reflecting personal knowing. Insights emerge bringing forth personal and professional knowing, about the art and science of holistic nursing. I explore the challenges in separating ourselves from personal knowledge and experience in reflective writing. I invite readers to take time to pause amidst a global healthcare pandemic to consider the potential of reflection to support nurses in recovering from suffering experienced during a pandemic.